Recepcija Cirila Kosmača pri študentih Pedagoške fakultete - Medved-Udovič, Vida (Jezik in slovstvo, 2014)
The article highlights the reception of Ciril Kosmač on the part of students of the Faculty of Education in Koper; the data were acquired by surveying 106 students of the 2011, 2012 and 2013 generations, all of whom had sat the secondary school-leaving Matura exam. The primary and secondary school curriculum for Slovenian and the current reading materials with excerpts from Ciril Kosmač served as the basis of the survey. The results show that the short story Tantadruj is among Kosmač's most popular works.
Keywords: Kosmač, Ciril; recepcija; učni načrt; berila